Development of Controlled-Release Formulation to Improve Bioavailability of Esomeprazole - Soujanya, C. (Asian Journal of Pharmaceutics (AJP), 2022)
Aim: The aim of this study was to release the active drug immediately after oral administration, to acquire quick, and enter systemic drug absorption. Such immediate-release products result in comparatively rapid drug absorption and onset of associated pharmacodynamic effects. Materials and Methods: The prepared esomeprazole CR tablets were evaluated for the dissolution studies in acid buffer (pH-1.2) for 2 h, 4.5 pH acetate buffers for 2 h, 6.8 pH phosphate buffers for 8 h, and 7.4 pH phosphate buffers for 12 h % drug release that was calculated at various time intervals. Results and Discussion: The present study was aimed to developing controlled-release tablets of esomeprazole using various polymers. All the formulations were evaluated for physicochemical properties and in vitro drug release studies. Conclusion: The current research work envisaged was an attempt to development of controlled-release formulations of esomeprazole to improve bioavailability.